Islamic feminism in response to the western misogyny, and women’s rights in the Islamic context - Rahman, H. M.Mahfuzur; Islam, Jahirul; Khan, Nasreen; Shamem, A. S. M.; Rashid, Md Harun (University of Jordan,Deanship of Scientific Research, 2025)
Objectives: This study explores the complex interaction between Islamic feminism and Western feminism, focusing on how Islamic feminism addresses claims of gender oppression in Muslim societies and challenges Western feminist critiques. It also investigates the rights Islam grants to women and the misconceptions surrounding these rights in Western discourse. Methods: Using a qualitative approach, the research examines feminist texts, Islamic scriptures, and historical accounts to analyze how Islamic feminism has developed as a response to Western narratives. It also evaluates feminist critiques and the socio-cultural impact of colonialism and neo-colonialism on gender discourse in Islamic societies. Results: The findings reveal that Islamic feminism emphasizes gender equality rooted in the Qur’an and challenges the patriarchal interpretations of Islamic teachings. It also highlights the misrepresentation of Muslim women in Western feminism, revealing instances of Islamophobia and cultural imperialism. Islamic feminism emerges as a framework that reclaims religious identity while advocating for gender justice. Conclusions: This study concludes that Islamic feminism provides a powerful counter-narrative to Western feminism by asserting the compatibility of gender equality with Islamic values. It underscores the need to recognize the agency of Muslim women and dismantle stereotypes perpetuated by Western frameworks, fostering a more inclusive and culturally sensitive understanding of feminism.